Mycotoxins and Food Safety 2020
DOI: 10.5772/intechopen.93213
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Application of Nanoparticles on Grains during Storage: Part 2 – An Overview of Inhibition against Fungi and Mycotoxin Biosynthesis

Abstract: Mycotoxins are secondary metabolites synthesized by filamentous fungi. They are common food contaminants that cause mycotoxicosis in humans and animals. Due to the severity of health risk pose by these mycotoxins, many countries have enacted strict measures to curb this menace. One promising measure is the use of nanoparticles. Herein, we present an overview of the application of titanium dioxide, chitosan, ultradisperse humic sapropel suspension, and carbon-based nanoparticles, a novel and innovative method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 201 publications
(210 reference statements)
0
2
0
Order By: Relevance
“…[ 15,16 ] In another study, the Ag‐NPs/TiO 2 composites were found to exhibit antibacterial properties by reducing enzyme activity, releasing silver ions, and altering the production of nicotinamide adenine dinucleotide phosphate hydrogen (NADPH). [ 17 ] Bactericidal activities were found to be caused by adsorption and penetration of Ag nanoparticles (Ag‐NPs) and toxicity caused by electrostatic interactions. [ 18 ] When nanoparticles are used, they could damage the membrane, create ROS, and change how well the cell wall lets water in.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15,16 ] In another study, the Ag‐NPs/TiO 2 composites were found to exhibit antibacterial properties by reducing enzyme activity, releasing silver ions, and altering the production of nicotinamide adenine dinucleotide phosphate hydrogen (NADPH). [ 17 ] Bactericidal activities were found to be caused by adsorption and penetration of Ag nanoparticles (Ag‐NPs) and toxicity caused by electrostatic interactions. [ 18 ] When nanoparticles are used, they could damage the membrane, create ROS, and change how well the cell wall lets water in.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to what is typically observed reported in literature. [ 17–23,37–41 ] This occurs because the metallic silver, which is essential for the recombination of electron–hole pairs on the surface of titanium dioxide (TiO 2 ), rapidly transforms into silver ions when exposed to aqueous solutions under aerobic circumstances. [ 42,43 ] However, this is not the case for the composite thin films of silver nanoparticles (Ag‐NP) and TiO 2 synthesized using the MPM.…”
Section: Introductionmentioning
confidence: 99%